A semi-analytical correlation of thermal-hydraulic-mechanical behavior of fractures and its application to modeling reservoir scale cold water injection problems in enhanced geothermal reservoirs. (November 2016) - Wang, Shihao; Huang, Zhaoqin; Wu, Yu-Shu; Winterfeld, Philip H.; Zerpa, Luis E.
Highlights: A semi-analytical correlation of the fracture aperture change induced by cold water injection has been derived. The correlation is of practical usage. The correlation has been implemented in a parallel geothermal simulator to conduct fully coupled thermal-hydraulic-mechanical simulation. The results predicted by the model has been used to qualitatively explain the increase of injectivity of cold water injectors and to predict the permeability variation in Cooper Basin. Abstract: Fractured enhanced geothermal system (EGS) reservoirs are typically sensitive to thermal and mechanical change induced by cold water injection. It has been observed that the permeability at the cold water injector is significantly enhanced. The physical thermal-hydrologic-mechanic (THM) process behind this phenomenon is that, the injection of cold water decreases the temperature of the reservoir rock and causes the matrix block to shrink, resulting in an increase of the fracture aperture and fracture permeability. Therefore, it is of great importance to quantify the effect of thermally induced fracture aperture change to better predict the behavior/performance of EGS reservoirs. In this work, we develop a novel correlation of the thermal-induced normal change of fracture aperture. The new correlation is based on the analytical solution of the governing displacement equations. Compared to the existing empirical correlations, the new correlation can better describe the physical processes by including the thermal effect on the matrix-fracture deformation. We have verified this correlation with respect to refined simulation results and implemented this correlation in a fully coupled massively parallel geothermal simulator, THM-EGS. We have applied this correlation to study field scale problems with certain parameters from Habanero Field in Copper Basin, Australia. Our results demonstrate that the fracture permeability near the cold water injector could be enhanced 7 times.